Adequacy of risk-reducing gynaecologic surgery in BRCA1 or BRCA2 mutation carriers and other women at high risk of pelvic serous cancer - Kiely, B. E. (Springer Netherlands, 2011)
The aim of this study was to describe the type of risk-reducing gynaecologic surgery (RRGS) and the extent of pathological evaluation being undertaken for Australasian women at high familial risk of pelvic serous cancer. Surgical and pathology reports were reviewed for women with BRCA1/BRCA2 mutations, or a family history of breast and ovarian cancer, who underwent RRGS between 1998 and 2008. “Adequate” surgery was defined as complete removal of all ovarian and extra-uterine fallopian tube tissue. “Adequate” pathology was defined as paraffin embedding of all removed ovarian and tubal tissue. Predictors of adequacy were assessed using logistic regression. There were 201 women, including 173 mutation carriers, who underwent RRGS. Of these, 91% had adequate surgery and 23% had adequate pathology. Independent predictors of adequate surgery were surgeon type (OR = 20; 95% CI 2–167; P = 0.005 for gynaecologic oncologists versus general gynaecologists), more recent surgery (OR = 1.33/year; 95% CI 1.07–1.67; P = 0.012) and younger patient age (OR = 0.93/year of age; 95% CI 0.87–0.99; P = 0.028). Independent predictors of adequate pathology were more recent surgery (OR = 1.26/year; 95% CI 1.06–1.49; P = 0.008) and surgeon type (OR = 3.1; 95% CI 1.4–6.7; P = 0.004 for gynaecologic oncologists versus general gynaecologists). Four serous ovarian cancers and one endometrioid endometrial cancer were detected during surgery or pathological examination. In conclusion Australasian women attending a specialist gynaecologic oncologist for RRGS are most likely to have adequate surgery and pathological examination. Additional education of clinicians and consumers is needed to ensure optimal surgery and pathology in these women.